Determinants of Uncontrolled Hypertension among Maritime Communities in Riau Islands, Indonesia: A Mixed-Methods Study on Social-Cultural and Self-Care Factors - Yulia Devi Putri; Nursyirwan Effendi; Adang Bachtiar; Harnavi Harun (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Background: Hypertension remains a significant health challenge in maritime communities due to unique occupational and cultural lifestyles. In the Riau Islands, the prevalence of hypertension reached 25.3% in specific coastal areas, yet control rates remain suboptimal. Objective: This study aims to analyze the factors influencing blood pressure control among hypertensive patients in a maritime setting. Methods: A quantitative cross-sectional study was conducted with 237 hypertensive respondents in the maritime area of Batam, Riau Islands. Data were collected using questionnaires covering demographics, knowledge, stress levels, medication adherence, and socio-cultural factors. Results: The majority of respondents were male (60.8%), aged 45–59 years (60.8%), and worked as fishermen (52.7%). Analysis showed that 74.3% of patients had uncontrolled hypertension. Significant determinants included low medication adherence (52.3%), high stress levels (62.4%), poor health knowledge (54.4%), and limited access to healthcare facilities (67.5%). Socio-cultural practices, particularly the high consumption of salted seafood and traditional beliefs, significantly hindered hypertension control (p < 0.05). Conclusion: Hypertension control in maritime populations is heavily influenced by socio-cultural habits and systemic barriers. Tailored interventions, such as the "Alviro Model," are necessary to address these specific coastal challenges.